Extrastriate visual areas integrate form features over space and time to construct representations of stationary and rigidly rotating objects - McCarthy, J. Daniel (J Cogn Neurosci, 2015)
When an object moves behind a bush, for example, its visible fragments are revealed at different times and locations across the visual field. Nonetheless, a whole moving object is perceived. Unlike traditional modal and amodal completion mechanisms known to support spatial form integration when all parts of a stimulus are simultaneously visible, relatively little is known about the neural substrates of the spatiotemporal form integration processes involved in generating coherent object representations from a succession visible fragments. We use fMRI to identify brain regions involved in two mechanisms supporting the representation of stationary and rigidly rotating objects whose form features are shown in succession: Spatiotemporal Form Integration (STFI) and Position Updating. STFI allows past and present form cues to be integrated over space and time into a coherent object even when the object is not visible in any given frame. STFI can occur whether or not the object is moving. Position updating allows us to perceive a moving object, whether rigidly rotating or translating, even when its form features are revealed at different times and locations in space. Our results suggest that STFI is mediated by visual regions beyond V1 and V2. Moreover, while widespread cortical activation has been observed for other motion percepts derived solely from form-based analyses (Krekelberg, Vatakis, & Kourtzi, 2005; Tse, 2006), increased responses for the position updating that leads to rigidly rotating object representations were only observed in visual areas KO and possibly hMT+, indicating that this is a distinct and highly specialized type of processing.